Aboriginal Traditions in the Treatment of Substance Abuse - McCormick, Rod M. (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper describes the traditions and philosophy behind successful substance abuse treatment strategies used by Aboriginal people in Canada. Disconnection from cultural values and traditions have led to a painful and meaningless existence for many Aboriginal people who have turned to drugs and alcohol in an unsuccessful attempt to deal with their anxiety and pain. The discovery of meaning and the resultant healing for Aboriginal clients is being enabled through substance abuse treatment strategies that facilitate reconnection to cultural values and traditions.